Cryo-EM in drug discovery. (15th January 2019) - Ceska, Tom; Chung, Chun-Wa; Cooke, Rob; Phillips, Chris; Williams, Pamela A.
Abstract : The impact of structural biology on drug discovery is well documented, and the workhorse technique for the past 30 years or so has been X-ray crystallography. With the advent of several technological improvements, including direct electron detectors, automation, better microscope vacuums and lenses, phase plates and improvements in computing power enabled by GPUs, it is now possible to record and analyse images of protein structures containing high-resolution information. This review, from a pharmaceutical perspective, highlights some of the most relevant and interesting protein structures for the pharmaceutical industry and shows examples of how ligand-binding sites, membrane proteins, both big and small, pseudo symmetry and complexes are being addressed by this technique.